Vibrational Study of the Hydrogen Adsorption on the Missing Row Platinum (110) Surface - Hanh, Tran Thi Thu; Hoa, Nguyen Van (Communications in Physics, 2020)
The hydrogen vibration was investigated to analyze its affect on the hydrogen adsorption on the missing row platinum surface (H/Pt(110)-(1\(×\)2) model) in the ultrahigh vacuum (UHV). The density functional theory (DFT) combined with the approximation oscillation of the hydrogen atom on the surface was used. When the hydrogen coverage ΘH on the surface is 100% (\(Θ\) = 1 ML), and taking into account the vibrational effect, the bond formed at the edge of the first layer (short bridge) is the most stable site. The vibrational effect on the adsorption model H/Pt(110)-(1\(×\)2) is significant.